Die Relevanz von Nähe: Wissensvernetzung in der maritimen Wirtschaft aus räumlicher, funktionaler und relationaler Perspektive - Bentlage, Michael; Wiese, Anne; Brandt, Arno; Thierstein, Alain; Witlox, Frank (Raumforschung und Raumordnung | Spatial Research and Planning, 2014)
The maritime economy as a heterogeneous innovation system has ongoing relevance to the successful spatial and functional development of regions in Europe. A strong technological knowledge base underpins the competitiveness of the maritime economy, which is grounded in distinct spatial structures and proximities. The simultaneous relevance of global and local knowledge is particularly pronounced in the maritime economy through its inherent relevance to globalization and structural change. Conventional classifications of the maritime economy embedded in the discussion of the spatialization of knowledge-intensive activities and global value chains, however, limit the analysis to certain parts of the maritime cluster. This paper examines the applicability of various discourses on interactive knowledge generation and application as a process, based on a comprehensive dataset derived from cooperative links within the maritime economy of northern Germany. It suggests a framework for analysis that is activity based and focuses on the concurrent presence of different dimensions of proximity across value-creating systems. We explore spatial patterns by means of social network analysis. These patterns are industry-specific and have the potential to inform efforts to increase functional as well as physical connectivity in regions. The empirical analysis begins with the individual firm as an actor seeking to optimize its location for the purpose of competitiveness. It proposes an approach that is rooted in the ongoing discussion on spatial and functional dispositions for innovation activity and that bridges the dichotomy of knowledge-intensive services and manufacturing activities in the maritime economy.